El hule: de los olmecas a los polímeros sintéticos - Vázquez Moreno, Flavio; Cruz Almanza, Raymundo; Ángeles Anguiano, Enrique; Olea Cardoso, Óscar; López Castañares, Rafael (CIENCIA ergo-sum, 2017)
-